Higher education ESL curriculum transition post-COVID-19 era: A systematic review - Rachel Ingkee Martin; Wardatul Akmam Din; Ameiruel Azwan Ab Aziz; Suyansah Swanto (Global Academic Excellence, 2021)
The COVID-19 pandemic has caused a stir in the field of education. As higher educational institution (HEI) closes its lecture halls and tutorial rooms due to the pandemic, lecturers in HEI are scrambling to adjust to the curriculum transition from having a face-to-face lecture to teaching remotely using an online platform. ESL instructors in HEI were among those affected by the sudden curriculum transition. Therefore, this paper aims to systematically review the challenges faced by ESL instructors from HEI on how they adapted to the curriculum transition post-COVID-19. Related articles were obtained from two prominent databases namely ProQuest and Scopus using specific keyword search terms. A total of six articles were selected for review out of 933 articles that were initially detected from the databases after executing a thorough selection criteria. After that, the challenges faced by ESL instructors and how they cope with the challenges were identified and discussed. Our findings suggest that ESL instructors from different parts of the world are all experiencing an adverse struggle in adapting to the curriculum transition caused by the COVID-19 pandemic. However, more studies in the context of ESL curriculum are needed to fully understand the impact of COVID-19 on ESL instructors’ teaching performance.